Deformation Modeling of Pyramidal Piles Base at Petroleum Industry Facilities - Zotsenko, Mykola; Vynnykov, Yuriy; Miroshnychenko, Iryna; Petrash, Ruslan (International Journal of Engineering and Technology, 2018)
Utilizing the comparison of results of mathematical modeling by the finite element method and from the field and laboratory studies, it has been determined that the compaction zone diameter of the short pyramidal piles by the exponential function is impacted by the internal friction angle of a soil. Within the limits of the axisymmetric spatial problem, the task was solved in a geometrically non-linear setting. It has been proved that utilizing the 8-nodal iso-parametric axisymmetric finite elements allows using both rectangular and curvilinear finite element grid. The elements varied in shape and volume, and accounting for these variations enables determining the displacements, stresses, and described soil properties at each stage of the piles' construction (or a cone head digging-in). It also has been established that the natural soil properties and geometrical size of operating devices do not have a significant influence on the modeling accuracy.Â